Presence of larva migrans in sand boxes of public elementary schools, Brazil - Nunes, Cáris M (2000)
There are sandboxes in public elementary school playground areas in Brazil, which can be harmful to children. They are at risk of cutaneous and visceral larva migrans infection caused by Ancylostoma spp. and Toxocara spp., respectively. The study was designed to investigate contamination by Toxocara spp. and/or their eggs and Ancylostoma spp. larvae in sand samples collected from the schools' sandboxes. Five hundred and thirty-five sand samples from 28 public elementary schools were collected during summer and winter and analyzed by both Baermann´s method and centrifugal flotation technique. Ancylostoma spp. larvae were found in 35.7% (10/28) schools in summer time and in 46.4% (13/28) schools in the winter time. Eggs of Toxocara spp. could not be recovered from the samples analyzed and eggs from Ancylostoma spp. were seen in 0.56% (3/535) of the samples.